Research on Influencing Factors and Improvement Strategies of Corporate ESG Performance from a Configuration Perspective - Wang, Keli (International Journal of Global Economics and Management, 2025)
There is a close relationship between ESG ratings and aviation companies. A higher ESG score can enhance the social image, brand value, and market competitiveness of aviation companies; At the same time, it also helps to reduce financing costs, enhance investor confidence, and promote the sustainable development of the industry. Using 21 aviation manufacturing A-share listed companies as case studies, the dynamic QCA method is adopted to further explore the configuration path of factors affecting the ESG score of aviation enterprises from the spatiotemporal dimension by processing and analyzing the financial panel data of enterprises from 2018 to 2023. Research has found that financial factors indirectly affect the ESG score of aviation companies, and there are three pathways that affect the ESG score of aviation companies, namely market structure, financial performance, and capital structure. The configuration of these three variables has a strong impact on the ESG score of aviation companies, and these impacts have complex and nonlinear characteristics.